2014
DOI: 10.1111/jch.12415
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sympathetic Denervation in Patients With Hypertension and Chronic Kidney Disease: Does Improvement in Renal Function Follow Blood Pressure Control?

Abstract: Twenty‐seven patients with resistant hypertension and chronic kidney disease were treated by renal sympathetic denervation (RSD) and followed for 12 months. Patients were retrospectively divided into controlled and uncontrolled blood pressure (BP) groups. Increases in mean estimated glomerular filtration rate (eGFR) were found at months 1, 3, 6, and 12 in the controlled group (P<.0001, for every time point). The mean change in eGFR after 12 months was 18.54±8.15 mL/min/1.73m2 higher in the controlled group (P=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
4
22
1
Order By: Relevance
“…This procedure has also proved effective in controlling resistant hypertension even in patients with CKD. In two studies with a short follow-up period, the RSD was associated with increased eGFR [31,34,35] and the reduction of albuminuria [31,34,36]. Our data confirm the results of previous studies in relation to improving the office BP, 24-hour ABPM, number of antihypertensive drugs, creatinine values, eGFR and ACR, at the 6 th month post procedure.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This procedure has also proved effective in controlling resistant hypertension even in patients with CKD. In two studies with a short follow-up period, the RSD was associated with increased eGFR [31,34,35] and the reduction of albuminuria [31,34,36]. Our data confirm the results of previous studies in relation to improving the office BP, 24-hour ABPM, number of antihypertensive drugs, creatinine values, eGFR and ACR, at the 6 th month post procedure.…”
Section: Discussionsupporting
confidence: 82%
“…As it is already known he control of BP reduces the rate of progression of CKD [31] and RSD is a powerful method for the control of resistant hypertension [32,33]. This procedure has also proved effective in controlling resistant hypertension even in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ott et al reported an observational pilot study in patients with CKD stages 3 and 4 which indicates that treatment of hypertension with renal sympathetic denervation (RSD) decreases BP and slows or even halts the decline of renal function [2], in agreement with our previous results that showed BP control and an increase in estimated glomerular filtration rate (eGFR), especially in the mild stages of CKD [3][4][5], after RSD. Subjects that were considered responders to RSD regarding renal function presented changes in eGFR with order of magnitude higher than 6.2% [4].…”
supporting
confidence: 82%
“…As we described previously [5,6], the reduction in office BP was evident from the 1st month until one year after RSD in refractory hypertensive patients. A recent study in animals showed the pathology of radiofrequencyderived RSD during the time and provided important knowledge of the mechanisms resulting in sustained BP reduction, and reported that the nerve damage post radiofrequency ablation was greatest at 7 days, with maximum functional nerve damage sustained ≤30 days.…”
mentioning
confidence: 71%